1987
DOI: 10.1111/j.1365-2621.1987.tb13973.x
|View full text |Cite
|
Sign up to set email alerts
|

Texture and Microstructure of Cooked Whole Egg Yolks and Heat‐Formed Gels of Stirred Egg Yolk

Abstract: Hardness, cohesiveness, and springiness of heated intact egg yolks were determined by an Ins&on compression test. Hardness increased as temperature was increased from 75" to 90°C and as time of heating was increased from 10 to 30 min. Cohesiveness and springiness increased as temperature was increased from 75" to 80°C and as time was increased from 10 to 30 min. Egg yolks from cooked shell eggs were lower in all textural parameters than gels formed from stirred egg yolk. Low scores for cohesiveness and springi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 9 publications
2
27
1
1
Order By: Relevance
“…These polyhedral granules were formed by yolk spheres with similar sizes. 25 The microstructure of salted egg yolk visualized by SEM indicated that polyhedral granules were aligned closely when the salting proceeded, mainly due to dehydration during salting, regardless of salting process. The greater the reduction in moisture content, the more tightly the granules were packed.…”
Section: Changes In Textural Properties Of Duck Egg During Saltingmentioning
confidence: 98%
“…These polyhedral granules were formed by yolk spheres with similar sizes. 25 The microstructure of salted egg yolk visualized by SEM indicated that polyhedral granules were aligned closely when the salting proceeded, mainly due to dehydration during salting, regardless of salting process. The greater the reduction in moisture content, the more tightly the granules were packed.…”
Section: Changes In Textural Properties Of Duck Egg During Saltingmentioning
confidence: 98%
“…Woodward and Cotterill (1987a) hypothesized that stirring caused changes in the microstructure of raw EY that resulted in changes in the textural properties of cooked EY. Fujii et al (1973) reported that EY in its native state consisted of yolk spheres packed tightly together in the form of polyhedral structures.…”
Section: Introductionmentioning
confidence: 99%
“…Woodward and Cotterill (1987) reported that egg white gel examined with SEM was very coarse with large irregularly shaped voids. Nevertheless, ovalbumin gels showed the homogeneous microstructure (Heertje & Van Kleef 1986).…”
Section: Discussionmentioning
confidence: 99%